Two new species of genus Hemipsocus (Psocodea: ‘Psocoptera’: Hemipsocidae) from India - Ramesh, Gurusamy; Babu, Rajappa; Subramanian, Kumarapuram A. (Zootaxa, 2025)
Two new species of Hemipsocus Selys-Longchamps, 1872 are described here based on specimens collected from the forests of Jharkhand, Kerala and Tamil Nadu states, India. The species, H. mockfordi sp. nov. and H. menoni sp. nov., are differentiated from other members of this genus by the following characteristics; the female subgenital plate with two apical lobes, the straight and strongly chitinized male paraproctal horn in H. mockfordi sp. nov. The male epiproct exhibits well-developed scales that extend from the anterior section towards the median region in H. menoni sp. nov.